STRATEGI GURU AQIDAH AKHLAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN: STRATEGI GURU AQIDAH AKHLAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - , Syamsuddin, Muhammad Miftah Jauhari (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This research explores the strategy of Aqidah Akhlak teachers in improving thequality of learning in MTs. Miftahul Maarif Kudus. With a descriptive qualitative approach,this study uses documentation, observation, and interviews in exploring data and datareduction, displaying data, and drawing conclusions in analyzing data, the results of thestudy show: first, students' understanding, evaluation of learning outcomes, development ofteacher strategies to actualize various potentials in his possession, showed goodqualifications. The implementation is carried out every semester 5 times with the aim of theimplementation being to get data and information about achieving competence. Second, theteacher's strategy in improving quality is by attending training, through independentlearning, reading books related to her field, and increasing his knowledge through otherrelevant media. Third, the factors that influence the strategy are time constraints, and thereare still students who have difficulty in learning. While the efforts of Aqeedah Moralteachers in improving the quality of learning are very good and endless with innovationsand fun tricks in learning, for example quizzes, additional learning methods.